Surgical Repair of Anomalous Origin of the Left Subclavian Artery From the Pulmonary Artery Using a Supraclavicular Approach. Issue 3 (May 2023) - Soynov, Ilya A.; Kulyabin, Yuriy Y.; Arkhipov, Alexey N.; Ivanzov, Sergey M.; Galstyan, Meline G.; Voitov, Alexey V.
Anomalous origin of the left subclavian artery from the pulmonary artery is a rare congenital cardiac malformation. We describe a case of anomalous origin of the left subclavian artery from the pulmonary artery in a patient who presented with symptoms of vertebrobasilar insufficiency and underwent reimplantation of the left subclavian artery into the left common carotid artery from the supraclavicular approach.